Students’ metacognitive activities in contextual mathematical problem solving - Wangguway, Yustinus; Nusantara, Toto; Sudirman, Sudirman; Susiswo, Susiswo (International Journal of Evaluation and Research in Education (IJERE), 2025)
Metacognition is essential in supporting students’ academic success, problem-solving abilities, and overall achievement. Therefore, this study aimed to provide a detailed description of metacognitive activities of students when engaging in contextual mathematical problem-solving. The participants comprised 11th-grade students from SMA Negeri 3 Jayapura, Papua Province, Indonesia. Descriptive and qualitative methods were adopted, and the data were collected using various test instruments and interview guidelines. Subsequently, the data were analyzed through the phases of reduction, presentation, as well as conclusions, and triangulation methods were used to ensure robustness and reliability. The results showed that metacognitive awareness occurred when students considered previous knowledge and experiences in solving contextual mathematical problem. Metacognitive evaluation activities occurred when relevant methods and steps were assessed, while metacognitive regulation manifested when contemplating the actions required to solve problem. This showed that students used various metacognitive activities, namely awareness, evaluation, and regulation, to address contextual mathematical problem.